P0: Progress to zero: A simple metric to measure COVID-19 progress by country/region - Lavista Ferres, Juan M.; Etzioni, Ruth B; Weeks, Bill (2020)
The current COVID-19 pandemic is having a devastating impact on the world. As of May 8th, 2020, more than half of the world is in lockdown, 3.6 million people have been infected, and over 250,000 of them have died. This is the first pandemic in human history that has been tracked on a daily basis across the world. Currently, progress is being tracked by a series of metrics, including new cases, deaths, and the effective reproduction number over time (R(t)), which epidemiologists have emphasized. While it is an important measure, R(t) is not observable and is dependent on the absolute number of active cases; therefore, two geographies could have a similar R(t) but be having very different experiences. Here, we propose a metric to monitor progress on addressing the COVID pandemic that we name "progress to zero" or P0. P0 corresponds to the percentage decline from a previously recorded peak level. The metric ranges from 0% (representing a geography that has not yet peaked) to 100% (representing a geography wherein 0 cases have been recorded for at least seven days). Our metric helps leaders focus on progress to a desired goal, easily can be tracked over time, can quickly identify retreat from progress, and is comparable across geographies regardless of their size.